Job satisfaction in small-scale fisheries: Comparing differences between Costa Rica, Puerto Rico and the Dominican Republic. (July 2020) - Partelow, Stefan; Seara, Tarsila; Pollnac, Richard B.; Ruiz, Victor
Abstract: This study analyzes and compares job satisfaction scores among small-scale fishers in the Gulf of Nicoya, Costa Rica over time. Data from Puerto Rico and the Dominican Republic is also compared to analyze changes in job satisfaction across cases, to unpack the explanatory factors leading to variation in job satisfaction scores. Factors such as gear type, age, education, years fishing, fishing regulations, fishery institutions and perceptions of governance, among others, are analyzed in terms of their relationships with three aggregate components of job satisfaction: Self-actualization, Health, and Earnings. Findings indicate changes over time in the Gulf of Nicoya as well as differences between countries. Fishers in Puerto Rico manifest high levels of job satisfaction when compared with the Dominican Republic and the Gulf of Nicoya. Differences appear to be influenced by gear type, with higher values on some aspects of job satisfaction being related to gears found most frequently in Puerto Rico and lower values associated with hand-line and long-line fishers frequently in the Gulf of Nicoya. Variation in extent and relative success of fishers' associations are also related to levels of job satisfaction. Governance aspects, including the presence of illegal fishing and conflicts between fishers using different gear, appear to have complex relationships with fishers' attitudes towards their occupation. In conclusion, we argue that understanding changes and variation in job satisfaction is critical for viewing the overall sustainability of fisheries.